2007
DOI: 10.1074/jbc.m609283200
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Protein C Receptor Acts as a Cellular Receptor for Factor VIIa on Endothelium

Abstract: Although factor VII/factor VIIa (FVII/FVIIa) is known to interact with many non-vascular cells, activated monocytes, and endothelial cells via its binding to tissue factor (TF), the interaction of FVII/FVIIa with unperturbed endothelium and the role of this interaction in clearing FVII/FVIIa from the circulation are unknown. To investigate this, in the present study we examined the binding of radiolabeled FVIIa to endothelial cells and its subsequent internalization. 125 I-FVIIa bound to non-stimulated human u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
211
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(226 citation statements)
references
References 35 publications
(30 reference statements)
12
211
2
Order By: Relevance
“…They also showed that blocking the EPCR binding site on the endothelial cell surface increased the generation of FXa. Further investigation is needed on this subject, as these results conflict with our own published (31) and unpublished data. At present, it is unknown whether FVIIa binding to EPCR either on non-stimulated or stimulated endothelium facilitates TFPI inhibition of FVIIa.…”
Section: Fviia Association With Epcr On Endotheliumcontrasting
confidence: 74%
See 3 more Smart Citations
“…They also showed that blocking the EPCR binding site on the endothelial cell surface increased the generation of FXa. Further investigation is needed on this subject, as these results conflict with our own published (31) and unpublished data. At present, it is unknown whether FVIIa binding to EPCR either on non-stimulated or stimulated endothelium facilitates TFPI inhibition of FVIIa.…”
Section: Fviia Association With Epcr On Endotheliumcontrasting
confidence: 74%
“…More FVIIa is endocytosed in cells expressing EPCR than in cells that lack EPCR. Furthermore, blocking EPCR on endothelial cells significantly reduces FVIIa internalization in HUVEC (31), suggesting that FVIIa association with EPCR facilitates FVIIa endocytosis. If this is confirmed in in vivo experiments using animal model systems, then novel therapeutic options to prolong circulatory levels of FVIIa might arise.…”
Section: Fviia Association With Epcr On Endotheliummentioning
confidence: 96%
See 2 more Smart Citations
“…Studies with unstimulated HUVEC showed that FVIIa associates with endothelial cells in a time-, temperature-and dose-dependent manner. The binding is calcium dependent but independent of TF and negatively charged phospholipids [3]. The N-terminus domain that contains γ-carboxyglutamic acid (Gla) residues is essential for FVIIa binding to endothelial cells.…”
Section: Fviia Interaction With Endothelial Cellsmentioning
confidence: 99%